Nyepi Lokal Dalam Pengejawantahan Pelestarian Alam di Desa Lokasari Kecamatan Sidemen Kabupaten Karangasem - Merta, Putu; Kanca Wijaya, Ketut (Jayapangus Press, 2022)
Nyepi Day is celebrated by Hindus in Indonesia. In the Province of Bali, where the majority of the population is Hindu, not only in Sasih Kesanga (the ninth month of the Balinese calendar) implement Nyepi, but in several districts in the Province of Bali, the villagers carry out Local Nyepi which is coupled with various ritual/ceremonial activities. Lokasari Village is one of the villages in Sidemen District, Karangasem Regency, Bali Province. The objectives to be conveyed in this paper are (1). To find out the background of the emergence of the Local Nyepi tradition which was held in Lokasari Village. (2). To find out what is the basis of the implementation of Local Nyepi which is held in Lokasari Village. (3). To find out the similarities and differences between the implementation of Local Nyepi and Nyepi carried out by Hindus in Indonesia in general. (4). To find out the community's perception of Local Nyepi which was held in Lokasari Village. The methods used in this paper are: observation, interviews, and literature study. So that the results of the Ngusabha Ceremony which are written in Lontar Dharma Pamacul and Lontar Widhi Sastra and Local Nyepi are obtained because of the tradition of the Lokasari Village community that has been passed down from generation to generation (dresta desa), the similarity lies in the implementation of Catur Brata Penyepian and is based on Tilem, the difference is in the timing of the ceremony, the series of activities for the Nyepi ceremony, the Nyepi executive committee, and its objectives. The purpose of implementing Ngusabha and Local Nyepi in Lokasari Village is seen as a purification ceremony for Bhuana Agung and Bhuana Alit as well as an expression of community gratitude for the harvest that has been obtained by the community.